FISH Diagnosis of Acute Graft-Versus-Host Disease Following Living-Related Liver Transplant - Kanehira, Kazunori (American Society for Investigative Pathology, 2009)
Acute graft-versus-host disease (GVHD) is an uncommon but often fatal complication following liver transplant. We describe a GVHD case in which a female patient with primary biliary cirrhosis underwent a living-related liver transplant from her son. The human leukocyte antigen typing of the donor was homozygous at all loci. The recipient's human leukocyte antigen type was haplo-identical to that of the donor. A bone marrow aspirate performed for pancytopenia revealed a severely hypoplastic marrow. Fluorescent in situ hybridization (FISH) using X- and Y-chromosome probes demonstrated that 80% of marrow cells were of donor origin. Comparison of Giemsa-stained cell morphology and FISH showed that the erythroid precursor cells were predominantly of male pattern (XY). This report is one of only a few studies that prove the migration of a donor's hematopoietic stem cells to a recipient's bone marrow. We demonstrated that FISH analysis using sex chromosome probes is useful to confirm a diagnosis of GVHD following organ transplantation from a donor of the opposite sex. We also showed that donor hematopoietic stem cells in a liver graft can migrate to the recipient's bone marrow. We suggest that FISH is a rapid and reliable test for confirming the diagnosis of GVHD in a peripheral blood or skin biopsy sample.